Influence of soil amendment of different concentrations of amino acid water-soluble fertilizer on physiological characteristics, yield and quality of “Hangjiao No.2” Chili Pepper - Emily Patience Bakpa (PeerJ Inc., 2021)
Amino acids are well known as natural stimulators of plant growth and are widely used to promote crop yield and quality. Several studies have been conducted to investigate the effects of amino acid (s) as a foliar spray on a variety of plant species. However, the effects of soil amendment of different concentrations of amino acid water-soluble fertilizer on the physiological characteristics, yield, and quality of pepper remain unclear. Following this, three experimental sets of amino acid water-soluble fertilizer in the ratio 1.8: 2.7: 3.6 kg including control (CK) were conducted in Lintao county, Gansu province. The treatments were applied through furrow method at 6 weeks after planting. The results showed that physiological characteristics of the pepper plants, such as chlorophyll a (1.35 mg g−1), and b (0.67 mg g−1), total chlorophyll (2.02 mg g−1), carotenoid (0.63 mg g−1), ETR (26.25 µmol m−2s−1), Fv/Fm (0.75), Qp (0.92) contents of the leaves were increased by the 1.8 kg treatment while NPQ (71.37%) and root activity (2185.52 µg g−1 h−1) were improved by the 3.6 kg treatment compared to the control. Fertilization with 2.7 kg of amino acid water-soluble fertilizer also had a significant influence on fruit length (25.50 cm), and yield of pepper (37.92 t ha−1) while fruit diameter (24.51 mm), firmness (5.30 kg cm−2), fresh (48.10 g) and dry (4.71 g) weights were higher in the 1.8 kg treatment compared to the control. The lowest rate of fertilizer (1.8 kg) applied again resulted in a significant increase in soluble protein (79.79%), capsaicin (5.80 mg g−1), dihydrocapsaicin (1.08 mg g−1), vitamin C (72.33%) and the essential and non-essential amino acid contents of the pepper which ranged from (235.15 to 11.16 µg g−1) and (1,605.10 to 16.63 µg g−1) respectively, while soluble sugar (9.02%) was enhanced by 3.6 kg treatment compared to the control. The findings suggest that soil amendment with low concentration of amino acid water-soluble fertilizer (1.8 kg) could be successfully used to improve the physiological characteristics and fruit quality of peppers in vegetable production.